A mineração artesanal e de pequena escala em pegmatitos e cerâmica no município de Parelhas, região do Seridó/Rio Grande do Norte - Melo, Rodrigo Otávio Freire de (2010)
The working conditions, occupational health, occupational illness and workers quality of life, usually referring to the artisanal activities and the workers with a poor professional support. Because this reality is still present in locals without good infrastructure of social and economic attention, there is a need for a broad knowledge of problems related to the productive processes that include features of unsanitary and unhealthy. Despite the intense process of industrialization promoted by globalization and the growth of developing nations like Brazil, the activities of artisanal and small-scale mining are still suffering from the marginalization of their production processes and their workers. This dissertation deals with the description of mineral-based activities (MBA), especially the activities related to production processes of extraction and processing of red pottery and minerals in pegmatites in Parelhas city, Seridó, Rio Grande do Norte, which are conducted by small mining companies or artisanal miners. The study of the work process was based on direct observation, photographic documentation, ergonomics, health and occupational safety analysis, interviews and structured questionnaire with workers of the two activities. The results indicate the need for improvement in both workplaces (red pottery and pegmatites), adaptation of workers to safety standards specific to the workplace, more attention and care related to ergonomics and occupational safety, greater importance to economic and social relations among performed activities, workers and firms of mineral branch and better and greater integration of social policies, supported by different sectors of society with the intention of transforming the current social, cultural, labor and education situation